Fabrication of highly ordered nanoarray electrode (patterned pvc with platinum nanoparticle) for ethanol electro-oxidation in alkaline medium - Zhao, Zhang (2018)
This report explains the detailed fabrication process of nanoarray on polyvinyl chloride (PVC) via thermal nano-imprint lithography, followed by electro-deposition of platinum nanoparticle on the nanoarray. The catalytic behavior of the final product on electro-oxidation of ethanol was investigated by using cyclic voltammetry. The patterned substrate with platinum nanoparticle showed significant improvement in the catalytic activity towards ethanol electro-oxidation reaction as compared to other non- patterned substrate and substrate without platinum loading.